2017
DOI: 10.1051/0004-6361/201628877
|View full text |Cite
|
Sign up to set email alerts
|

Molecular transitions as probes of the physical conditions of extragalactic environments

Abstract: Aims. We present a method to interpret molecular observations and molecular line ratios in nearby extragalactic regions. Methods. Ab initio grids of time dependent chemical models, varying in gas density, temperature, cosmic ray ionization rate, and radiation field, are used as inputs into RADEX calculations. Tables of abundances, column densities, theoretical line intensities, and line ratios for some of the most used dense gas tracers are provided. The degree of correlation as well as degeneracy inherent in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…This suggests two possibilities: 1) the HCN/HCO + enhancements trace an alternate physical process than AGN activity, or 2) these MIR classified starbursts host AGN that are behind obscuring screens sufficiently thick to render MIR diagnostics ineffective. The former is supported by theoretical work showing that differences in the HCN/HCO+ line intensity ratios can arise due to many different densities, temperatures, radiation fields, and evolutionary states of activity (e.g., Viti 2017). The latter scenario is plausible as the necessary optical depths are seen in the "compact obscured nuclei" (CONs; Sakamoto et al 2010;Aalto et al 2015;Falstad et al 2015;Scoville et al 2015) which can have obscuring columns in excess of N H > 10 25 cm −2 and show emission from vibrationally excited HCN molecules (HCN-VIB).…”
Section: Dense Molecular Gas Tracers and Active Galactic Nucleimentioning
confidence: 87%
See 1 more Smart Citation
“…This suggests two possibilities: 1) the HCN/HCO + enhancements trace an alternate physical process than AGN activity, or 2) these MIR classified starbursts host AGN that are behind obscuring screens sufficiently thick to render MIR diagnostics ineffective. The former is supported by theoretical work showing that differences in the HCN/HCO+ line intensity ratios can arise due to many different densities, temperatures, radiation fields, and evolutionary states of activity (e.g., Viti 2017). The latter scenario is plausible as the necessary optical depths are seen in the "compact obscured nuclei" (CONs; Sakamoto et al 2010;Aalto et al 2015;Falstad et al 2015;Scoville et al 2015) which can have obscuring columns in excess of N H > 10 25 cm −2 and show emission from vibrationally excited HCN molecules (HCN-VIB).…”
Section: Dense Molecular Gas Tracers and Active Galactic Nucleimentioning
confidence: 87%
“…During Phase III (1 − 2 Myr) the cosmic ray flux is reduced back to the Galactic value and the chemical evolution is followed; this phase is intended to approximate the molecular gas chemistry after rapid cessation of SMBH accretion. We note that these models are general and it is not appropriate to compare these values with observed intensity ratios; the models do not include any observational considerations, including resolution effects (see e.g., Viti 2017). ing, the chemical evolution may be much slower. Thus, HCN enhancements can persist long past the time in which an AGN has turned off, consistent with our finding that HCN enhancements are poor indicators of current SMBH growth.…”
Section: Radiative Pumping Of Hcnmentioning
confidence: 99%
“…We have in fact compared the abundances of the main nitrogen-bearing species, their isotopologues and the fractionation ratios and found that in small cases the behavioural trends remain unchanged. We ran UCLCHEM in two phases in a very similar manner as in Viti (2017) where theoretical abundances for extragalactic studies were derived. In Phase I, the gas is allowed to collapse from a diffuse atomic state (∼ 10 cm −3 ) up to a high density (chosen by the user) by means of a free-fall collapse.…”
Section: Chemical Modelling Of Carbon Fractionationmentioning
confidence: 99%
“…Cl + 1.0(-9) F 6.68(-9) * Increasing oxygen abundance corresponds to decreasing oxygen depletion for dark cloud conditions (Hincelin et al 2011). have also been used to determine time-dependent column densities, benchmark chemical networks and models, and predict molecular emission line intensities in starburst galaxies from statistical equilibrium calculations in the LVG approximation (Viti 2017). We automate the execution of the Nautilus code (Ruaud, Wakelam, and Hersant 2016) over a 7-D parameter space (gas kinetic temperature T gas , density n, visual extinction A V , cosmic ray ionization rate ζ, dust temperature T dust , reactive desorption efficiency a, and diffusion to binding energy ratio b), as shown in Table 1, and for each molecule i we construct a 9-D data structure {X i , t, T gas , n, A V , ζ, T dust , a, b} containing the abundance X i at every time t and every combination p of free parameters {T gas , n, A V , ζ, T dust , a, b}.…”
Section: Grid Modelsmentioning
confidence: 99%